Phagocytosis of PLGA microparticles in rat peritoneal exudate cells: A time-dependent study - Gomes, Anderson de Jesus; Lunardi, Claure Nain; Caetano, Flavio Henrique; Lunardi, Laurelucia Orive; da Hora Machado, Antonio Eduardo (Cambridge University Press, 2006)
With the purpose of enhancing the efficacy of microparticle-encapsulated therapeutic agents, in this study we evaluated the phagocytic ability of rat peritoneal exudate cells and the preferential location of poly(D,L-lactide-co-glycolic acid) (PLGA) microparticles inside these cells. The microparticles used were produced by a solvent evaporation method and were characterized by dynamic light scattering (DLS), transmission electron microscopy (TEM), and scanning electron microscopy (SEM). Size distribution analysis using DLS and SEM showed that the particles were spherical, with diameters falling between 0.5 and 1.5 mu m. Results from cell adhesion by SEM assay, indicated that the PLGA microparticles are not toxic to cells and do not cause any distinct damage to them as confirmed by the MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide) assay. Among the large variety of cell populations found in the peritoneal exudates (neutrophils, eosinophils, monocytes, and macrophages), TEM showed that only the latter phagocytosed PLGA microparticles, in a time-dependent manner. The results obtained indicate that the microparticles studied show merits as possible carriers of drugs for intracellular delivery.
Keywords: microparticles; drug delivery; peritoneal exudate cells; macrophage; TEM; SEM